Bibles and Bathrooms: Intersex Variation Awareness Among College-Aged American Christians - Lusk, Jeniece (2022)
The extant literature concerning the existence and experience of the LGBTQIA+ community in the United States sometimes overshadows that of people with intersex variations (Jones, 2018). While many people with intersex variations identify within the binary, these variations directly challenge belief systems conforming to the existence of only two sexes, and thus, only two relative genders. This research attempts to gain a greater understanding of American awareness, acceptance, and attitudes concerning intersex variations, and how these beliefs fit into or challenge conservative views of gender. More specifically, we focus on the relationship between religiosity and views of homosexuality, and how these variables may influence and/or be influenced by intersex variation awareness and acceptance. Using a survey of 146 American college students, we find that overall intersex variation is viewed with more acceptances and comfort than homosexuality, and that Christians (in particular, those leaning toward biblical literalism) are more likely to express views that those with intersex variations should adhere to sex and gender binaries.